Terror from behind the keyboard: conceptualising faceless detractors and guarantors of security in cyberspace. Issue 1 (2nd January 2016) - Mott, Gareth
ABSTRACT: By reflecting on active public-domain government documents and statements, this article seeks to develop securitisation theory's articulation of the dichotomy between legitimate and illegitimate violence as it is reflected in British government policy. This dichotomy has (re)developed through a process wherein GCHQ and MI5 are portrayed as "faceless guarantors" of security, in Manichean juxtaposition to the discursively created phantom cyberterrorists, who are presented as "faceless detractors" of security. It has previously been stated that the terrorism discourse associated with the present "War on Terror" is attributed, in part, to mechanics of fantasy. I argue that, within the securitised discourse of cyberterrorism, the limits of fantasy possesses a murky nuance, which in turn, allows for a deeper – or at least more entrenched – securitisation. The official discourse surrounding the intelligence services' online surveillance apparatus operates with a similar opaque quality, but this is upheld by securitising actors as a strength to be maintained.